Becoming RBG : Ruth Bader Ginsburg's journey to justice - Levy, Debbie (Simon & Schuster Books for Young Readers, 2019)
Presents a graphic novel biography of U.S. Supreme Court Justice Ruth Bader Ginsburg, celebrating her rise to prominence and blazing of trails for women in the traditionally male-dominated spheres of education and law.